High-k dielectric for flexible pressure sensors - Foo, Fang Hao (Nanyang Technological University, 2024)
Flexible capacitive pressure sensors have gained significant attention owing to their simple design and wide range of applications in wearable electronic devices. Several examples of these applications include healthcare and electronic skin, which are pivotal for advancements in areas like artificial intelligence. In this project, a flexible capacitive sensor with flexible substrate and electrode is designed using hafnium oxide as its dielectric, which is a high-k dielectric material rather than typical dielectric elastomers. The hafnium oxide layer will be deposited using Atomic Layer Deposition (ALD). A quality of the ALD film prepared is first verified using the traditional silicon substrate and metallic electrodes (rigid materials), and characterisation of the dielectric layer was done via Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM), for extracting the thickness and elemental composition characterisation, respectively. Eventually, the constructed flexible capacitive pressure sensor showed high capacitance densities (≈ 1470 nF/cm2), which translated to good dielectric constant values (≈ 16.6). Additionally, it also displayed reasonable sensitivity values (≈ 3.46 kPa-1).